Interaction of the amyloid precursor protein‐like protein 1 (APLP1) E2 domain with heparan sulfate involves two distinct binding modes. (1st March 2015) - Dahms, Sven O.; Mayer, Magnus C.; Roeser, Dirk; Multhaup, Gerd; Than, Manuel E.
<x xml:space="preserve">Abstract</x> Beyond the pathology of Alzheimer's disease, the members of the amyloid precursor protein (APP) family are essential for neuronal development and cell homeostasis in mammals. APP and its paralogues APP‐like protein 1 (APLP1) and APP‐like protein 2 (APLP2) contain the highly conserved heparan sulfate (HS) binding domain E2, which effects various (patho)physiological functions. Here, two crystal structures of the E2 domain of APLP1 are presented in the apo form and in complex with a heparin dodecasaccharide at 2.5 Å resolution. The apo structure of APLP1 E2 revealed an unfolded and hence flexible N‐terminal helix αA. The (APLP1 E2)2–(heparin)2 complex structure revealed two distinct binding modes, with APLP1 E2 explicitly recognizing the heparin terminus but also interacting with a continuous heparin chain. The latter only requires a certain register of the sugar moieties that fits to a positively charged surface patch and contributes to the general heparin‐binding capability of APP‐family proteins. Terminal binding of APLP1 E2 to heparin specifically involves a structure of the nonreducing end that is very similar to heparanase‐processed HS chains. These data reveal a conserved mechanism for the binding of APP‐family proteins to HS and imply a specific regulatory role of HS modifications in the biology of APP and APP‐like proteins.